Security and Privacy in Multi-Cloud Environments - Mahajn, Shubham; Khandelwal, Somya; Muskan (International Journal of Psychosocial Rehabilitation, 2020)
In the modern-day panorama of computing, the adoption of multi-cloud environments has emerge as increasingly more commonplace, providing businesses stronger flexibility, scalability, and resource optimization. However, this proliferation introduces complex demanding situations related to safety and privateness. This research makes a speciality of examining the intricacies of protection and privacy concerns within multi-cloud setups, mainly addressing demanding situations and featuring solutions inside the geographical regions of facts encryption, identification control, and compliance. A important mission in multi-cloud environments is the implementation of powerful statistics encryption strategies throughout numerous systems. Protecting data confidentiality and integrity as it traverses distinctive cloud offerings is of paramount importance. This have a look at seriously evaluates present encryption methodologies, assesses their suitability in multi-cloud scenarios, and indicates progressive tactics to reinforce records safety. Identity control emerges as another important factor of the multi-cloud safety paradigm. The secure orchestration of user identities throughout disparate cloud services needs cautious exam. This studies explores the complexities surrounding identification federation, authentication mechanisms, and get entry to controls inside multi-cloud environments. By figuring out vulnerabilities and proposing strong identity management solutions, the study contributes to the improvement of secure multi-cloud infrastructures. Additionally, making sure compliance with regulatory frameworks and industry standards poses a powerful venture in multi-cloud protection. The examine scrutinizes the complex panorama of compliance necessities, encompassing diverse geographical and enterprise-specific policies. By analyzing the gaps and intricacies in present compliance frameworks, the research proposes a comprehensive method to make sure adherence to guidelines whilst operating in a multi-cloud environment. In conclusion, this studies addresses the challenges and solutions inherent in ensuring strong protection and privacy measures within multi-cloud environments. By specializing in facts encryption, identity management, and compliance, the observe provides valuable insights for companies navigating the complex terrain of multi-cloud computing.